Long-term monitoring of the non- native giant river prawn Macrobrachium rosenbergii (De Man, 1879) in the Furnas mega reservoir (southeastern Brazil) - Chaves, Ana Julia de Padua; Zara, Fernando Jose [UNESP]; Paschoal, Lucas Rezende Penido [UNESP] (Soc Brasileira Carcinologia, 2023)
In this study, we report six records of the non-native giant river prawn Macrobrachium rosenbergii (De Man, 1879) in the Furnas mega reservoir, state of Minas Gerais (Southeast Brazil), during continuous monitoring conducted from 2006 to 2023. All recorded specimens were males of the blue claw (BC) morphotype and possibly entered interior areas of the reservoir via accidental escapes. There was no occurrence of established populations in the region, nor any evidence of disease in the specimens obtained. However, continuous monitoring is recommended to record new escapes and determine the possibility of establishment of giant river prawn populations in the aquatic environment of the Furnas mega reservoir.
Keywords: Bio-invasion; Caridea; escapes; Neotropical region; new records